Үерийн долгионы шилжилтийн Маскингем загварын Нэшийн хувилбарыг Хэрлэн голын савд туршсан үр дүн - Д, Оюунбаатар; Т, Цэнгэл (Scientific transaction of the National University of Mongolia. Physics, 2022)
Since its development around 1934 by McCarthy(1938), the Muskingum method has been one of the most popular methods for routing flood waves in rivers. ...